Clinical and Functional Characteristics of a Novel KLF11 Cys354Phe Variant Involved in Maturity-Onset Diabetes of the Young - Yujing Sun; Jingru Qu; Jing Wang; Ruxing Zhao; Chuan Wang; Li Chen; Xinguo Hou (Journal of Diabetes Research)
Background. Mutations in human KLF11 may lead to the development of maturity-onset diabetes of the young 7 (MODY7). This occurs due to impaired insulin synthesis in the pancreas. To date, the clinical and functional characteristics of the novel KLF11 mutation c.1061G > T have not yet been reported. Methods. Whole-exon sequencing was used to screen the proband and family members with clinical suspicion of the KLF11 variant. Luciferase reporter assays were used to investigate whether the KLF11 variant binds to the insulin promoter. Real-time PCR, western blotting, and glucose-stimulated insulin secretion (GSIS) analysis were used to analyze the KLF11 variant that regulates insulin expression and insulin secretion activity in beta cell lines. The Freestyle Libre H (Abbott Diabetes Care Ltd) was used to dynamically monitor the proband daily blood glucose levels. Results. Mutation screening for the whole exon genes identified a heterozygous KLF11 (c.1061G > T) variant in the proband, her mother, and her maternal grandfather. Cell-based luciferase reporter assays using wild-type and mutant transgenes revealed that the KLF11 (c.1061G > T) variant had impaired insulin promoter regulation activity. Moreover, this variant was found to impair insulin expression and insulin secretion in pancreatic beta cells. The proband had better blood glucose control without staple food intake (p<0.05). Conclusions. Herein, for the first time, we report a novel KLF11 (c.1061G > T) monogenic mutation associated with MODY7. This variant has impaired insulin promoter regulation activity and impairs insulin expression and secretion in pancreatic beta cells. Therefore, administering oral antidiabetic drugs along with dietary intervention may benefit the proband.